Critical Analysis of in situ Performance of Glass Fiber Core VIPs in Extreme Cold Climate - Chan, Vivian Ting Ting; Ooms, Matthew D.; Korn, Juergen; MacLean, Douglas; Mooney, Stephen; Andre, Shane; Mukhopadhyaya, Phalguni (Frontiers in Energy Research, 2019)
Glass fiber core vacuum insulation panels (VIPs) are becoming an increasingly attractive option for building envelope construction due to lower cost and availability around the world. Although fumed silica core VIPs have shown superior long-term performance under accelerated aging tests compared to glass fiber core VIPS, these laboratory test results have yet to be verified with long-term field performance data. In 2011, glass fiber core VIPs were installed in a commercial building retrofit project in Yukon, Canada (one of Canada’s most northern territories), and have been continuously monitored since. This paper summarizes the thermal performance of the glass fiber core VIPs over the period of 2011 – 2018 in an extreme cold climate. Findings from this study provided data to validate glass fiber core VIP accelerated aging test results and the aging rate of VIPs in a cold and dry climate was determined. These results will help developing a better understanding of the long-term performance of glass fiber core VIPs in a real-world context.